Auditoría de gestión, al gobierno autónomo descentralizado municipal de Paquisha, período 01 de enero al 31 de diciembre del 2013 - Medina Tamayo, Jackelinne Alexandra (2015)
This research work called "AUDIT OF MANAGEMENT, THE HOME GOVERNMENT DECENTRALISED MUNICIPAL Paquisha, PERIOD 01 JANUARY TO 31 DECEMBER 2013", was developed with the firm intention of contributing to the design and implementation of management indicators, which to assess compliance with the goals, objectives, programs and activities planned by the company and prepare an audit report, containing comments, conclusions and recommendations. To meet the objectives, several interviews and surveys township officials Paquisha was used, then clear questions was applied through internal control questionnaires, in order to determine the reliability thereof and by applying audit methods and techniques, it was possible to detect significant findings, to analyze and describe them using narrative bonds and establish the different indicators, which allowed us to evaluate the efficiency, effectiveness and economy of staff activities, and then make comments and conclusions that generate timely, tending to take action and help the achievement of goals and objectives established by the institution recommendations. The results found when performing the audit process, are part not evaluate or periodically trains staff, does not have adequate control of entry and exit of personnel; no strategic plan to all staff spreads, is not complied with the provisions of the internal regulations, among others. As should take corrective measures to monitor and verify compliance with the responsibilities designated to each official of the entity; these being addressed timely management of the institution, for taking adequate corrective areas examined